2022
DOI: 10.4103/joacp.joacp_650_20
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of endotracheal tube size in the pediatric age group by ultrasound: A systematic review and meta-analysis

Abstract: Anatomical differences in the airway in pediatric patients, compared to adults pose many challenges during endotracheal intubation, such as selecting the proper sized endotracheal tube (ETT) during intubation. Our primary objective was to assess how accurate is ultrasound (US) co-relation in comparison to standard age-based formulas in pediatric patients. Meta-analysis was registered in PROSPERO 2020, CRD42020220041. Online literature available in PubMed, Cochrane, and Embase, Goggle scholar was searched from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…16 A recent meta-analysis of 18 pediatric studies concluded that ultrasound is an effective and reproducible technique for predicting ETT size in children (r value .824, 95% CI 0.677-0.908). 17 In our experience, this modality is particularly helpful for patients with inaccurate conventional age-based methods, such as premature infants, children with subglottic stenosis, or children who are small for age.…”
Section: Selection Of Appropriate Endotracheal Tube Sizementioning
confidence: 99%
“…16 A recent meta-analysis of 18 pediatric studies concluded that ultrasound is an effective and reproducible technique for predicting ETT size in children (r value .824, 95% CI 0.677-0.908). 17 In our experience, this modality is particularly helpful for patients with inaccurate conventional age-based methods, such as premature infants, children with subglottic stenosis, or children who are small for age.…”
Section: Selection Of Appropriate Endotracheal Tube Sizementioning
confidence: 99%
“…Using airway ultrasound, the subglottic diameter can be directly measured[ 59 ]. A recent meta-analysis showed that airway ultrasound can accurately predict tracheal tube size estimates, unlike the usual age or height-based formulas used in pediatric patients[ 60 ]. The minimal transverse diameter of the cricoid cartilage level was reported to be important to select the tracheal size for ventilation setting[ 61 ].…”
Section: Can Airway Ultrasound Be Used To Predict Tracheal Tube Size?mentioning
confidence: 99%
“…The pediatric patient group's tracheal structure is more specific [1][2][3]. Under eight years of age, unlike the adult larynx, the narrowest region of the larynx is the cricoid cartilage, and the cricoid has no flexibility (rima glottidis is the narrowest region in the adult) [1]. Accordingly, choosing the appropriate endotracheal tube (ETT) in pediatric patients is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing the suitable and appropriate intubation tube is of great importance in preventing complications that may occur in the particular pediatric airway [2]. 1 2…”
Section: Introductionmentioning
confidence: 99%